2020
DOI: 10.1186/s12895-020-00117-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations of self-reported atopic dermatitis with comorbid conditions in adults: a population-based cross-sectional study

Abstract: Background The objective of this study was to investigate the relationships between atopic dermatitis (AD) and other common chronic health conditions in adults. Methods A cross-sectional survey was sent to a randomly selected population sample of 78,004 adults in Sweden. The questionnaires included measures of self-reported physical and mental health. Binary and multinomial logistic regression were used to examine the associations of AD with common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Not only gut-skin axis, but also gut-brain axis might play a key role in the relation between gut microbiota and AD, patients with AD being at increased risk of psychological wellbeing issues. 58 In our study, we found that 29% of the contrasted functional modules between D0 and D18 were specific to the gut-brain axis modules, whereas they represent only 18% of all considered modules. Among the different modules associated to gut-brain axis, modules related to GABA are of particular interest.…”
Section: Discussionmentioning
confidence: 51%
“…Not only gut-skin axis, but also gut-brain axis might play a key role in the relation between gut microbiota and AD, patients with AD being at increased risk of psychological wellbeing issues. 58 In our study, we found that 29% of the contrasted functional modules between D0 and D18 were specific to the gut-brain axis modules, whereas they represent only 18% of all considered modules. Among the different modules associated to gut-brain axis, modules related to GABA are of particular interest.…”
Section: Discussionmentioning
confidence: 51%
“…Arterial hypertension (AH) represents the most common cardiovascular risk factor and is a prevalent comorbidity in adult patients with AD [ 31 ].…”
Section: Arterial Hypertensionmentioning
confidence: 99%
“…13 In adulthood, a comparable association between AD and asthma can be found. 14 Ethnic background has a differential impact on the expression of those diseases. For example, in AD, the clinical manifestation can be completely different among Asian, African American and European patients.…”
Section: T Ype Infl Ammati On: Where Doe S It Fit ?mentioning
confidence: 99%
“… 13 In adulthood, a comparable association between AD and asthma can be found. 14 Atopy, another critical phenotypic trait, is defined by the propensity of an individual to develop a specific IgE response against harmless antigens. As a part of AR definition, nasal symptoms need to be consistent with specific IgE production and/or cutaneous prick tests.…”
Section: Type 2 Inflammation: Where Does It Fit?mentioning
confidence: 99%